Centralisation and long-term change in farming regimes: Comparing agricultural practices in Neolithic and Iron Age south-west Germany - Styring, A; Rösch, M; Stephan, E; Stika, H; Fischer, E; Sillmann, M; Bogaard, A (Cambridge University Press, 2017)
This study uses two novel archaeobotanical techniques – crop carbon and nitrogen isotope analysis and functional weed ecology – to determine directly how the intensity of agricultural practice changed from the Neolithic to the early Iron Age in south-west Germany, with the emergence of fortified hilltop settlements (Fürstensitze or chiefly seats) regarded as the first urban centres in central Europe. The crop isotope and functional weed ecological evidence suggest that surplus cereal production in the early Iron Age was achieved through sustained use of manure combined with expansion in arable cultivation, both developments that are connected with more widespread use of animal traction. The increased scale of cultivation is broadly apparent across rural as well as fortified hilltop centres in the early Iron Age, and considerable variability in manuring intensity is consistent with agricultural decision-making at a local level rather than centralised control. Additionally, the more intensive manuring of hulled six-row barley, used in beer production, demonstrates that the political importance of drinking and feasting in early Iron Age society was reflected in crop husbandry practices. In terms of animal husbandry, faunal isotope data reveal a radical decrease in forest cover, potentially reflecting an expansion in the scale of herding accompanying that of arable cultivation. Site-specific patterning points to a range of herding strategies, from specialised herding of cattle at the Heuneburg to generalised patterns of livestock management at rural sites.